A CROSS SECTIONAL STUDY FOR THE EVALUATION OF PULMONARY EMBOLISM IN UNEXPLAINED DYSPNEA IN ACUTE EXACERBATION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - HUSSAIN, M; RAHIM, F; HABIB, G; ALI, MA; KHAN, MS; SABA, NU (Biological and Clinical Sciences Research Journal, 2024)
Infections are a common cause of Chronic Obstructive Pulmonary Disease (COPD) exacerbations, however, unexplained dyspnoea may be due to factors such as Pulmonary embolism (PE). In the cases of congenital diseases, early diagnosis of PE plays an important role mainly as regards morbidity and mortality. This work aims to determine the rate of PE in patients of COPD presenting with unexplained dyspnoea during exacerbations. Objectives: to assess the suspicion of Pulmonary thromboembolism in patients with COPD during acute exacerbation with unrevealing dyspnea and to compare clinical consequences and risk elements involved. A Cross-sectional study. The study was conducted from 21 June 2024 to 20 December 2024 at, Diagnostic Radiology Department, Sandamen Provincial Hospital Quetta. Methods: This cross-sectional study comprises 150 COPD patients having acute exacerbation and unexplained dyspnea. Participants had clinical assessments taken, D-dimer measurement and computed tomography pulmonary angiography (CTPA) done for the diagnosis of PE. The following patients were excluded from the study; patients with known factors that precipitated dyspnea. Statistical methods were used to analyze the data and in all the tests, a significance level of p < 0. 05 was used in this study. Results: Out of the total 150 patients, 28 patients were diagnosed with PE which accounts for 18. 6%. Regarding the mean age, the patients were 65 ± 7. 3 years of age. PE-positive patients had significantly elevated D-dimer levels as compared to the control group (p = 0. 03). The measure of dispersion for D- dimer levels was 220 ng/mL. Patients with PE had higher heart rates (mean ± SD: In addition, another study revealed that such patients present with higher heart rates (average of 102 ± 12 bpm) than patients without PE (p = 0. 01). Conclusions: Pulmonary embolism is well-known to be a cause of ‘Shortness of breath ’ in COPD exacerbation and it was present in almost one-fifth of the patients in this study. CTPA can help in early identification for most patients in the study and thus enhance their overall clinical prognosis for COPD patients, especially during exacerbations for which routine screening using the D-dimer test should be encouraged.